Features of state regulation of the organization of transportation process in modern conditions - Yessengeldina, A.S.; Sitenko, D.A.; Kantureev, M.T.; Amirovа, A.U. (KSU Publ., 2017)
The article reveals the role and peculiarities of the transportation process in the transport system. Forms and methods of state regulation of the organization of transportation in the Republic of Kazakhstan are considered. The duties of the carrier in the transportation of goods, passengers, baggage, postal items and in the implementation of transportation and forwarding services are characterized. The authors classified transportation by the following features: by type of transportation; by type of transport used; by industry; by type of messages; by execution time. The proposed classification does not only regulates a set of quality indicators, but also characterizes the strategy of the organization of transportation, and its evaluation with subsequent control impact. The production indicators, the ratio of income from freight and passenger transportation of the activities of the Joint Stock Company «National Company» Kazakhstan TemirZholy», which has a holding structure based on ensuring the functional integrity and controllability of the railway industry in the transportation process, are analyzed. The specifics of the application of the integrated system of regulation and control of material and information flows are determined. The possibilities of application of modern methods of intermodal (multimodal) transportations for increasing the efficiency of the domestic transport complex and enhancing its integration into the world transport system are explored. Proposals on the use of RFID equipment for the creation of a tracking system for locomotives, passenger and freight cars are given.
Қазіргі жағдайдағы тасымалдарды ұйымдастыру үдерісін мемлекеттік реттеудің ерекшеліктері
Особенности государственного регулирования процесса организации перевозок в современных условиях
Keywords: government regulation; government regulation; transport; freight; passenger; control; monitoring